(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
The focus of the current study is analyze the impact of the use of ICT on the performance of Tunisian companies. These companies must be always fully aware of the importance of a practical valorization of ICTs that bring about socio-economic development. Thus, using ICTs on Tunisian companies’ performance has unquestionably remained a vital need. In fact, this study is carried out on a sample of 150 Tunisian companies operating in different business sectors. We chose the quantitative method. So, to test our conceptual model, we applied the exploratory factor analysis and then the structural equation methods. The empirical testing of hypotheses of this research led to partially confirm the influence of ICTs on the performance of Tunisian companies. In this regard, the companies surveyed are almost aware of the importance of the value of ICT, which implies an insufficient use of ICTs and an incomplete maturity of this field.